2022
DOI: 10.1108/ijchm-02-2022-0210
|View full text |Cite
|
Sign up to set email alerts
|

Killing the service fire: leader aggressive humour undermines hospitality employees’ proactive customer service performance

Abstract: Purpose Drawing on research on organisation-based self-esteem (OBSE) and self-consistency theory, this study aims to investigate whether, how and when leader aggressive humour (LAH) impacts hospitality employees’ proactive customer service performance (PCSP). Design/methodology/approach A total of 294 supervisor–employee dyads from eight hotels in China participated in the survey. The data were analysed by hierarchical multiple regression and PROCESS macro in SPSS. Findings LAH undermines hospitality emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Jiang et al (2016) identified “doing things right” (ethical climate) and “doing things well” (service climate) as two essential climates that foster high-quality customer service in service organizations. Building upon the current context of the service industry, characterized by rapidly evolving customer needs and intensified competition (Ji et al , 2022; Sun et al , 2023), we introduce an additional critical component of superior service: “doing things proactively” (initiative climate). By integrating these three dimensions of organizational climates, namely, doing things right, well and proactively, we present a more comprehensive model of organizational climates in service organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al (2016) identified “doing things right” (ethical climate) and “doing things well” (service climate) as two essential climates that foster high-quality customer service in service organizations. Building upon the current context of the service industry, characterized by rapidly evolving customer needs and intensified competition (Ji et al , 2022; Sun et al , 2023), we introduce an additional critical component of superior service: “doing things proactively” (initiative climate). By integrating these three dimensions of organizational climates, namely, doing things right, well and proactively, we present a more comprehensive model of organizational climates in service organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al (2016) have demonstrated the significance of ethical and service climates as two important cultural aspects within service organizations, reflecting the values of “doing things right” and “doing things well,” respectively. Given the rapidly evolving customer needs and intensely competitive environment, service organizations today must foster employee initiatives to achieve superior service quality and ensure sustainable organizational growth (Ji et al , 2022; Sun et al , 2023). Therefore, we propose the addition of an initiative climate, which signifies the value of “doing things proactively.” By considering these three climates, we can gain a comprehensive understanding of the cultural mechanisms through which CEO responsible leadership influences the service industry.…”
Section: Introductionmentioning
confidence: 99%
“…During role performances at work, hospitality workers express themselves cognitively and employ themselves mentally and emotionally (Cooper et al, 2018;Harjanti, 2019). Leaders are viewed as pleasant and easy to work with when they use positive humor in their routine interactions, suggesting it is a motivational force (Sun et al, 2023;Tiwari and Jha, 2022). Therefore, we expect pro-socially motivated individuals to be resourceful and more likely to generate and apply innovative ideas in their workplace (Grant and Shandell, 2022).…”
Section: Role Of Pro-social Motivationmentioning
confidence: 98%
“…Therefore, humor in leaders may positively impact work outcomes (like IWB). According to Celestine and Yeo (2021), using the relational aspect of humor can generate essential ideas for managerial effectiveness and employee outcomes (Neves and Karagonlar, 2020; Sun et al ., 2023).…”
Section: Literature Reviewmentioning
confidence: 99%